Rancangan Aplikasi Game Pengenalan Anggota Tubuh Manusia Menggunakan Construct 2 di SDN Pandat 1 Berbasis Android - Refi Mulyadi; Basuki Rakhim Setya Permana; Ummy Kalsum (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Learning about human body parts at the elementary school level generally still relies on conventional methods, such as lectures and the use of textbooks. These methods often make students less interested and have difficulty understanding the material in depth. However, in the early childhood development stage, learning should be carried out with an approach that involves interaction, visualization, and fun activities. Therefore, innovative learning media are needed that can combine educational and entertainment elements (edutainment) to make the material easier to understand while increasing learning motivation. This study aims to design and develop an Android-based educational game application using Construct 2 aimed at helping students of SDN Pandat 1 learn human body parts interactively. The research method used is the Multimedia Development Life Cycle (MDLC) which consists of six stages: concept, design, material collection, creation, testing, and distribution. Research data were collected through direct observation in class, interviews with teachers, and documentation of learning activities. The resulting application contains material on human body parts presented in the form of text, images, animations, and is equipped with interactive quizzes to measure student understanding. Test results show that the application can run well on various Android devices with an attractive appearance and navigation that is easy for children to use. Student trials showed increased interest in learning and understanding of the material. Teacher responses were also positive, particularly regarding the app's ease of use and its alignment with the elementary school curriculum. These findings indicate that game-based learning media can be an effective alternative for improving the quality of learning, particularly in materials requiring visual and interactive conceptual understanding.